Molecular investigation of Staphylococcus aureus isolated from the patients, personnel, air and environment of an ICU in a hospital in Tehran - Mehdi Mirzaii; Mohammad Emaneini; Fereshteh Jabalameli; Shahnaz Halimi; Morovat Taherikalani (Elsevier, 2015)
Summary: Background: The aim of this study was to determine the prevalence and characteristics of Staphylococcus aureus isolates from the patients, staff, air and environments of an ICU in a hospital in Tehran. Materials and methods: During this study, 37 S. aureus isolates were collected and analyzed via the spa typing method. Results: Of the 37 S. aureus isolates, 35 (94%) were methicillin resistant (MRSA), 28 (76%) were identified as SCCmec types III or IIIA, four (10%) were identified as SCCmec types I or IA and three (8%) were identified a SCCmec type IV. All of the MRSA isolates were resistant to oxacillin and contained mecA. The isolates were all spa typed and found to comprise 11 spa types, including t7688, t7689, and t7789, which have not previously been reported. The spa type t7688 was isolated from the hands of two ICU personnel. The spa type t7689 was observed among five isolates from the air and the environment. The spa type t7789 was observed among three isolates from the patients, ventilators and the air. The majority of the isolates (43%) belonged to spa types t030 and t037. Conclusion: Our results revealed that MRSA strains that were isolated from the air, the environment of the ICU and the patients who were colonized or infected with MRSA often exhibited the same spa and SCCmec types. These results also reveal that the isolates from the patients and environment were usually indistinguishable. Keywords: MRSA, SCCmec III, Spa type, Tehran